2019
DOI: 10.3390/ijms20061448
|View full text |Cite
|
Sign up to set email alerts
|

Instability of Alien Chromosome Introgressions in Wheat Associated with Improper Positioning in the Nucleus

Abstract: Alien introgressions introduce beneficial alleles into existing crops and hence, are widely used in plant breeding. Generally, introgressed alien chromosomes show reduced meiotic pairing relative to the host genome, and may be eliminated over generations. Reduced pairing appears to result from a failure of some telomeres of alien chromosomes to incorporate into the leptotene bouquet at the onset of meiosis, thereby preventing chiasmate pairing. In this study, we analysed somatic nuclei of rye introgressions in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…The isolation of nuclei was performed according to [62]. Nuclei in G 1 , G 2 , or S phase of the cell cycle were identified and sorted while using a FACSAria II SORP flow cytometer (BD Biosciences, San Jose, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…The isolation of nuclei was performed according to [62]. Nuclei in G 1 , G 2 , or S phase of the cell cycle were identified and sorted while using a FACSAria II SORP flow cytometer (BD Biosciences, San Jose, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Another interesting issue that needs examination is the positioning of maize centromere(s) and telomeres in the somatic and meiotic nuclei of OMA plants. Inferred from the findings of Pernickova et al [31], telomere and centromere positioning can have implications for the ability of maize chromosomes to participate in the formation of the leptotene bouquet and consequently, the transmission rate of chromosome additions to the next generations of OMA plants.…”
Section: Discussionmentioning
confidence: 98%
“…It has been suggested that the retention of the added chromosomes might be dependent on their position in the hybrid nucleus. A recent study indicated that improper positioning of the introgressed alien chromosomes in nuclei may negatively affect their ability to migrate into the leptotene bouquet at the onset of meiosis, resulting in pairing failure and, consequently, in the loss of such chromosomes [31]. In wheat × rye introgression lines, the frequency of rye telomere misplacement in somatic nuclei was almost identical to the frequency of out-of bouquet rye telomere position in leptotene, indicating that there may be a systemic failure of some rye telomeres to assume proper positions in the wheat × rye nucleus [46].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While introgressed rye chromosomes or chromosome arms occupied discrete positions similar to chromosomes of the wheat host, their telomeres frequently occupied improper positions. This feature probably impacts the ability of introgressed chromosomes to migrate into the telomere bouquet at the onset of meiosis, leading to their gradual elimination over generations [12]. Non-denaturing fluorescence in situ hybridization (ND-FISH) was used to identify small segment translocations after irradiation in a wheat-rye 6RL Ku minichromosome addition line.…”
mentioning
confidence: 99%